THE INDEPENDENCE OF EXTERNAL AUDITOR IN INDONESIAN FINANCIAL SECTOR THROUGH PERFORMANCE MANAGEMENT SYSTEM - Maria Cindy Adisti Putri; Bettine Bergmans (Diponegoro Journal of Accounting, 2021)
In a finding, the performance management system will significantly affect audits' quality in an organization. Moreover, the quality of an audit is influenced by the independence of an external auditor. We believe that the performance management system can affect the independent behavior of an external auditor as a constructive improvement tool. In this study, the researcher will focus on the independence of the Financial Services Authority in Indonesia in conducting audit supervision of banks. This thesis aims to see whether the performance management system in the Financial Services Authority in Indonesia has been effective and continues to be a constructive tool by evaluating the performance of these state-owned institutions. The researcher used a literature review method as a research method by analyzing scientific and professional journals, reports, news, and research. The researcher also used the interview method to find information from experts in the Financial Services Authority in Indonesia.